Molecular Interaction Study on Binary Mixture of Phenol in Dioxane, Methanol and Acetonitrile at 303 K - MULLAINATHAN, S.; NITHIYANANTHAM, S.; RAJESEKARAN, M. (Asian Journal of Chemistry, 2010)
The ultrasonic velocity (U), density (ρ) and viscosity (η) at 303 K have been measured in the binary system of phenol in dioxane, methanol and acetonitrile. The acoustical parameters such as adiabatic compressibility (β), free length (Lf), free volume (Vf), internal pressure (πi), Wada's constant (W), Rao's constant (R) and acoustical impedance (Z) are calculated. The results are interpreted in terms of molecular interaction between the components of the mixtures.